An assessment of gene‐by‐environment interactions in developmental dyslexia‐related phenotypes. (24th November 2012) - Mascheretti, S.; Bureau, A.; Battaglia, M.; Simone, D.; Quadrelli, E.; Croteau, J.; Cellino, M. R.; Giorda, R.; Beri, S.; Maziade, M.; Marino, C.
Abstract : While the genetic and environmental contributions to developmental dyslexia (DD) have been studied extensively, the effects of identified genetic risk susceptibility and of specified environmental hazardous factors have usually been investigated separately. We assessed potential gene‐by‐environment (GxE) interactions on DD‐related reading, spelling and memory phenotypes. The presence of GxE effects were investigated for the DYX1C1, DCDC2, KIAA0319 and ROBO1 genes, and for seven specified environmental moderators in 165 nuclear families in which at least one member had DD, by implementing a general test for GxE interaction in sib‐pair‐based association analysis of quantitative traits. Our results support a diathesis‐stress model for both reading and memory composites: GxE effects were found between some specified environmental moderators (i.e. maternal smoke during pregnancy, birth weight and socio‐economic status) and the DYX1C1 ‐1259C/G marker. We have provided initial evidence that the joint analysis of identified genetic risk susceptibility and measured putative risk factors can be exploited in the study of the etiology of DD and reading‐related neuropsychological phenotypes, and may assist in identifying/preventing the occurrence of DD. Abstract : In the present study, we investigated the presence of GxE effects for the DYX1C1, DCDC2, KIAA0319 and ROBO1 genes, and for 7 specified environmental moderators in 165 nuclear families in which at least one member had DD, by implementing a general test for GxE interaction in sib pair‐based association analysis of quantitative traits. Our results support a diathesis‐stress model for both reading and memory composites: GxE effects were found between some specified environmental moderators (i.e., maternal smoke during pregnancy, birth weight, and socio‐economic status) and both the allelic variants of the DYX1C1‐1259C/G marker.